2015
DOI: 10.1039/c4py01565g
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of carbon nanotubes by combination of mussel inspired chemistry and SET-LRP

Abstract: Surface modification of carbon nanotubes by the combination of mussel inspired chemistry and SET-LRP has been reported for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 63 publications
0
51
0
Order By: Relevance
“…Also, bare SWCNTs are hydrophobic and require surface modification to prevent aggregation into bundles 4 that are deleterious to cells. 13,14 Recently, our group 9,15,16 and many others [17][18][19][20][21][22][23][24][25][26] have developed biologically relevant SWCNT dispersions using noncovalently linked block copolymers such as Pluronic s F-127 (PF127), biomolecules such as DNA and proteins, including bovine serum albumin (BSA), g-globulin, etc., and combinations such as polymers grafted onto polydopamine. 1,2 However, covalent alterations destroy the desirable thermal, electrical, mechanical and optical properties of individualized SWCNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Also, bare SWCNTs are hydrophobic and require surface modification to prevent aggregation into bundles 4 that are deleterious to cells. 13,14 Recently, our group 9,15,16 and many others [17][18][19][20][21][22][23][24][25][26] have developed biologically relevant SWCNT dispersions using noncovalently linked block copolymers such as Pluronic s F-127 (PF127), biomolecules such as DNA and proteins, including bovine serum albumin (BSA), g-globulin, etc., and combinations such as polymers grafted onto polydopamine. 1,2 However, covalent alterations destroy the desirable thermal, electrical, mechanical and optical properties of individualized SWCNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al [27] have developed an adhesive and transferable free-standing film with dual function of osteoinductivity and antibacterial activity, which is obtained by sequentially assembling vancomycin immobilized oxidized sodium alginate and dexamethasone encapsulated chitosan-coated BSA nanoparticles on a poly-dopamine layer. Our previous reports also have demonstrated that surface modification of different materials via mussel-inspired chemistry and Michael addition reaction [28][29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 93%
“…It has been demonstrated that DA can be self-polymerized under alkaline solution to form polydopamine (PDA) films, which can be adhered to almost any solid surface without surface pretreatment [46][47][48][49][50][51][52][53][54][55]. For example, the surface modification of silica capillary with NH 2 -PEG was demonstrated by Wang et al Results showed that the novel coating could provide effective suppression of EOF and minimized adsorption of proteins.…”
Section: Introductionmentioning
confidence: 94%